Clinical competency: perceptions of nursing interns and clinical mentors - Prathibha Jackline; Pai Radhika R.; George Linu Sara (Sciendo, 2024)
To assess the clinical competency of nursing interns and the perception of clinical nurse mentors toward student nurses' clinical competency.